2011
DOI: 10.1016/j.ydbio.2010.12.005
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans Dicer interacts with the P-granule component GLH-1 and both regulate germline RNPs

Abstract: P granules, ribonucleoprotein (RNP) complexes specific to the cytoplasmic side of the nuclear pores of C. elegans germ cells, are implicated in post-transcriptional control of maternally-transcribed mRNAs. Here we show a relationship in C. elegans of Dicer, the riboendonuclease processing enzyme of the RNA interference and microRNA pathways, with GLH-1, a germline-specific RNA helicase and a constitutive component of P granules. Based on results from GST-pull-downs and immunoprecipitations, GLH-1 binds DCR-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 72 publications
(96 reference statements)
4
45
2
Order By: Relevance
“…Third, many passively bound mRNAs encode RNA-granule-associated genes, and we show that Dicer protein itself is granularly localized in the C. elegans germline. Taken together with the observation that Dicer is required for RNP granule formation ( Figure S5D and Beshore et al, 2011), this indicates that passive binding may be important for RNA localization and assembly of RNA-protein complexes. This finding could explain the diverse although overall weak effects observed upon DICER1 knockdown in HEK293 cells and suggests that germ cells, forming prominent RNP structures, are a more suitable system to investigate this aspect of Dicer biology.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Third, many passively bound mRNAs encode RNA-granule-associated genes, and we show that Dicer protein itself is granularly localized in the C. elegans germline. Taken together with the observation that Dicer is required for RNP granule formation ( Figure S5D and Beshore et al, 2011), this indicates that passive binding may be important for RNA localization and assembly of RNA-protein complexes. This finding could explain the diverse although overall weak effects observed upon DICER1 knockdown in HEK293 cells and suggests that germ cells, forming prominent RNP structures, are a more suitable system to investigate this aspect of Dicer biology.…”
Section: Discussionsupporting
confidence: 72%
“…The association of passive Dicer binding with RNA granules suggests a role in mRNA localization. Indeed, our FLAG-tagged DCR-1 protein recapitulates the granular localization of wild-type DCR-1 in the C. elegans germline ( Figures 5K and S5E and Beshore et al, 2011).…”
Section: Passive Sites Can Interfere With Catalytic Dicer Activitymentioning
confidence: 68%
See 2 more Smart Citations
“…Some reports have suggested that it is as a component of germline perinuclear P--granule structures which are sites of mRNA export and possibly degradation (KAWASAKI et al 1998;SHETH et al 2010), and others have shown that these P--granules' structure or stability depends, at least indirectly, on RNAi components including CSR--1, EGO--1, DCR--1, DRH--3, PRG--1, and RDE--4 (BESHORE et al 2011;CLAYCOMB et al 2009;SPIKE et al 2008; UPDIKE and STROME 2009). While PGL--1's link to RNAs is genetically and biochemically well--established (HANAZAWA et al 2011;SCHISA et al 2001), especially for those in the germline, there are conflicting reports on its role in RNAi.…”
Section: Pgl--1's Link To Rnaimentioning
confidence: 99%